2013
DOI: 10.1088/0953-8984/25/24/246003
|View full text |Cite
|
Sign up to set email alerts
|

Jumps in entropy and magnetic susceptibility at the valence and spin-state transition in a cobalt oxide

Abstract: A wide family of cobalt oxides of formulation (Pr 1−y Ln y ) 1−x Ca x CoO 3 (Ln being a lanthanide) exhibits a coupled valence and spin-state transition (VSST) at a temperature T*, which involves two concomitant modifications: (i) a change in the spin state of Co 3+ from low-spin (T < T*) to a higher spin-state (T > T*), and (ii) a change in the valence state of Pr, from a mixed Pr 4+ /Pr 3+ state (T < T*) to a purely trivalent state (T > T*), accompanied by an equivalent charge transfer within the Co 3+ /Co 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In the bulk (Pr 1-x RE y ) 1-x Ca x CoO 3 systems under ambient pressure, which show the simultaneous MI-SS transition, a volume contraction of $1% took place below T MI $ 100 K. 44 The entropy change makes DS $ 5 JÁK À1 Ámol À1 , 45,46 which means that the internal energy of the low-temperature phase is about DSÁT MI $ 500 JÁmol À1 lower, compared with the high-temperature phase. The present PYCCO films are fixed on the substrate and the lattice parameters and the unit cell volume are difficult to change.…”
Section: Discussionmentioning
confidence: 99%
“…In the bulk (Pr 1-x RE y ) 1-x Ca x CoO 3 systems under ambient pressure, which show the simultaneous MI-SS transition, a volume contraction of $1% took place below T MI $ 100 K. 44 The entropy change makes DS $ 5 JÁK À1 Ámol À1 , 45,46 which means that the internal energy of the low-temperature phase is about DSÁT MI $ 500 JÁmol À1 lower, compared with the high-temperature phase. The present PYCCO films are fixed on the substrate and the lattice parameters and the unit cell volume are difficult to change.…”
Section: Discussionmentioning
confidence: 99%
“…A decade ago, Tsubouchi et al [1, 2] observed a metal-insulator transition in Pr 0.5 Ca 0.5 CoO 3 associated with a drop of magnetic susceptibility and a sharp peak in the specific heat indicating the collective nature of the transition. Subsequently, the transition was observed in other PCCO materials with x and y in the ranges 0.2-0.5 and 0-0.3, respectively [3][4][5]. Despite the evidence for a continuous, or very weakly first order, phase transition and the experimental effort [6] no long-range order could be identified.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…A quite unique type of transition takes place in a class of mixed valent cobalt oxides, involving both a change in the mean valence of cobalt (Co 3+ /Co 4+ ) and in the spin state of Co 3+ (low-spin/high-spin) (for an overview, see for instance [1,2] and references therein). This «valence and spin state transition» (VSST) strongly impacts all the physical properties, e.g., the magnetic susceptibility, the heat capacity, as well as the electrical and thermal conductivities [3][4][5][6][7][8][9][10][11][12]. There is no change of space group associated to this transition, but one observes a large reduction in the unit cell volume when crossing the VSST upon cooling [3,10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%